2009
DOI: 10.1016/j.bbi.2009.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide alters the blood–brain barrier transport of amyloid β protein: A mechanism for inflammation in the progression of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) brains are characterized by accumulation of amyloid-ß protein (Aβ) and neuroinflammation. Increased blood-to-brain influx and decreased brain-to-blood efflux across the blood-brain barrier (BBB) have been proposed as mechanisms for Aß accumulation. Epidemiological studies suggest that the nonsteroidal anti-inflammatory drug (NSAID) indomethacin slows the progression of AD. We hypothesized that inflammation alters BBB handling of Aß. Mice treated with lipopolysaccharide (LPS) had increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
162
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(174 citation statements)
references
References 58 publications
(74 reference statements)
9
162
3
Order By: Relevance
“…98,196 In a mouse lacking the antioxidant vitamin E, LRP-1-dependent brain efflux and systemic clearance of Ab are impaired. 197 Both LRP-1 and Pgp are functionally downregulated in the BBB in mice with systemic inflammation induced by LPS, 66,198 and this corresponds with impaired Ab efflux. 66,198 In contrast to AD, decreased function of these transporters after LPS was not attributed to reduced protein levels or oxidative damage.…”
Section: Alzheimer's Disease Risk Factors and The Blood-brain Barriermentioning
confidence: 99%
See 2 more Smart Citations
“…98,196 In a mouse lacking the antioxidant vitamin E, LRP-1-dependent brain efflux and systemic clearance of Ab are impaired. 197 Both LRP-1 and Pgp are functionally downregulated in the BBB in mice with systemic inflammation induced by LPS, 66,198 and this corresponds with impaired Ab efflux. 66,198 In contrast to AD, decreased function of these transporters after LPS was not attributed to reduced protein levels or oxidative damage.…”
Section: Alzheimer's Disease Risk Factors and The Blood-brain Barriermentioning
confidence: 99%
“…197 Both LRP-1 and Pgp are functionally downregulated in the BBB in mice with systemic inflammation induced by LPS, 66,198 and this corresponds with impaired Ab efflux. 66,198 In contrast to AD, decreased function of these transporters after LPS was not attributed to reduced protein levels or oxidative damage. 66 Despite this, the antioxidant N-acetylcysteine (Nac) was found to protect against LPS-induced Ab efflux impairment and LRP-1 dysfunction, but not Pgp dysfunction in the BBB.…”
Section: Alzheimer's Disease Risk Factors and The Blood-brain Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…LPS may play a role in A accumulation and AD progression. Intraperitoneal injections of LPS to mice alters the BBB transport of A protein through increasing blood-to-brain influx, decreasing brain-to-blood efflux and increasing neuronal A production (Jaeger et al, 2009). Other studies showed that intraperitoneal injections of LPS to mice could also lead to serious memory problems (Kahn et al, 2012;Lee et al, 2008).…”
Section: Leaky Gut Leaky Brain and Admentioning
confidence: 99%
“…In particular, imaging (25) and animal modelling (23,26) studies in AD suggest BBB dysfunction is an early event in the course of disease and may contribute to its pathogenesis, perhaps as a result of impaired amyloid-² clearance or associated neuroinflammation (23,(27)(28)(29)(30)(31). Furthermore, neuropathology studies report complex vascular changes associated with BBB dysfunction in AD (32)(33)(34), with evidence of a correlation between histological evidence of BBB leakage and Alzheimer-type pathologies in 'normal' ageing (35).…”
Section: Introductionmentioning
confidence: 99%